Prevalence and predictors of falls in a health‐seeking older population: An outpatient‐based study - Subramanian, Manicka Saravanan (Aging Med (Milton), 2020)
BACKGROUND: Falls are one of the major causes of disability in older people. A wide range of risk factors for falls are described according to setting – inpatient, nursing homes and community. The aim of this study was to identify the risk factors for falls in an outpatient setting. METHODS: In this cross‐sectional observational study, 160 consenting subjects were enrolled randomly, from the Geriatric Medicine outpatient department, All India Institute of Medical Sciences, New Delhi, India. Non‐ambulatory, seriously ill subjects were excluded. The subjects underwent brief evaluation including falls and geriatric assessment. They were grouped into fallers and non‐fallers. A multivariable logistic regression analysis was used to identify the factors associated with falls. RESULTS: The prevalence of falls was 23.75% (38/160). Women were proportionately higher (26.31%) in the fallers group vis‐à‐vis 19.67% in the non‐fallers group. After multivariate analysis, opioids (odds ratio [OR] 5.24 [95% CI, 2.0 18‐13.611]), vision impairment (OR 2.71 [95% CI, 1.050‐07.011]), fear of falling (OR 3.17 [95% CI, 1.167‐08.629]), instrumental activity of daily living (IADL) impairment (OR 3.41 [95% CI, 1.251‐09.301]), anti‐anginal medications (OR 8.90 [95% CI, 0.997‐79.564]) and self‐employment (OR 5.37 [95% CI, 1.058‐27.329]) were associated with falls. Adequate nutrition (OR 0.82 [95% CI, 0.688‐00.976]) and caregiver support (OR 0.46 [95% CI, 0.275‐00.801]) were protective of falls. CONCLUSION: We identified the multi‐factorial etiology of falls. Patients having any of the above risk factors should undergo detailed fall risk assessment and preventive measures afterwards.